2021
DOI: 10.1021/acs.bioconjchem.1c00487
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytically Stable Maleimide-End-Functionalized Polymers for Site-Specific Protein Conjugation

Abstract: Site-specific conjugation to cysteines of proteins often uses ester groups to link maleimide or alkene groups to polymers. However, the ester group is susceptible to hydrolysis, potentially losing the benefits gained through bioconjugation. Here, we present a simple conjugation strategy that utilizes the amide bond stability of traditional 1-ethyl-3-(3-dimethylaminopropyl)­carbodiimide/N-hydroxysuccinimide coupling while introducing site specificity. Hydrolytically stable maleimide-end-functionalized polymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The impact of polymer attachment site on cellulase activity and stability was investigated through site-specific thiol-Michael click chemistry of a library of polymers to wild-type and mutated Fn Cel5a. As shown in a previous study, wild-type Fn Cel5a has one reactive cysteine residue on the surface of the enzyme at position 319 . In addition to this, four lysine residues at various positions around the enzyme were individually mutated to cysteine residues to create K94C, K159C, K190C, and K300C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of polymer attachment site on cellulase activity and stability was investigated through site-specific thiol-Michael click chemistry of a library of polymers to wild-type and mutated Fn Cel5a. As shown in a previous study, wild-type Fn Cel5a has one reactive cysteine residue on the surface of the enzyme at position 319 . In addition to this, four lysine residues at various positions around the enzyme were individually mutated to cysteine residues to create K94C, K159C, K190C, and K300C.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Various approaches also exist for attaching the polymer to the protein, with the formation of amides by attachment to lysine residues or thiol-Michael adducts by attachment to cysteine residues in the protein being arguably the most common method. 40,41 In a previous study, we found that the conjugation of well-defined functional polymers to the lysine groups of FnCel5a results in enhanced activity without sacrificing stability due to electrostatic noncovalent interactions between the attached polymer and substrate. 42,43 Here, we investigate the impact of polymer length, charge, location site, and conjugation strategy on FnCel5a enzymatic activity and stability.…”
Section: ■ Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a typical carbodiimide reaction, the coupling reagent (i.e., EDC, DCC, DIC, etc.) is added in excess to ensure high conjugation efficiency (Pan et al, 2012;Biju, 2014;Wang et al, 2014;Gandhi et al, 2016;Zhang et al, 2016;Kuo et al, 2017;Palmieri et al, 2018;Shipunova et al, 2018;Wang et al, 2018;Elzahhar et al, 2019;Lim et al, 2019;Shiu et al, 2021;Wright et al, 2021), which leads to a highly activated carboxylate environment in the reaction medium. All primary amines within the peptide can participate in nucleophilic addition-elimination regardless of relative reactivities in such environments.…”
Section: Indirect Peptide Quantification Assays Provide Misleading Co...mentioning
confidence: 99%